Promosi Desa Wisata Hijau Berbasis Blogger di Desa Muara Tiga Kecamatan Mulak Ulu Kabupaten Lahat - Sulastri Sulastri; Ratu Aisyah Ratih Primaputri; Alditya Aris Rinandy; Akhmad Ghozali (Penerbit Goodwood, 2026)
Purpose: This community service program aims to improve the digital promotion capacity of the local community in Muara Tiga Village, Mulak Ulu District, Lahat Regency, by developing blogger-based promotional media to support the development of a green tourism village. Research Methodology: The program was implemented through several stages, including preliminary socialization, training on digital literacy and blog creation, practical mentoring sessions, and evaluation using pre-test and post-test instruments. Participants consisted of members of the youth organization and local tourism awareness groups. The evaluation focused on measuring participants’ understanding of digital literacy, blog management, and online content promotion. Results: The results show that participants demonstrated a significant improvement in their understanding of digital literacy concepts and blogging practices. The average correct response rate increased from 30.7%–84.6% in the pre-test to 75%–100% in the post-test. Conclusions: The blogger-based training program successfully enhanced participants’ digital literacy and their ability to promote the tourism potential of Muara Tiga Village through online platforms. Limitations: The program was implemented in a single village with a limited number of participants and assessed only short-term learning outcomes, so the long-term impact of blogger-based promotion on tourism visibility and community economic benefits remains unmeasured. Contributions: This program contributes to strengthening community-based tourism promotion strategies and supports the development of digital-based green tourism villages, particularly in rural areas with limited access to digital promotion too.